A Systematic Literature Review on Risk Factors in Software Development Outsourcing - Abd Wahab, Alawiyah; Piak San, Teh (International Journal of Engineering and Technology, 2018)
Software development outsourcing has become a prevalent practice in the software industry. Organizations in both public and private sectors are adopting software development outsourcing in order to achieve lower cost and to access to skilled labour. However, it is widely recognized that outsourced software development projects involve risks and sometimes leads to undesirable consequences. Existing research in the software engineering and related areas have identified several risks in the software development outsourcing projects such as lack of communication and technical skills. The aim of this paper is to examine the literature on outsourced software development in order to identify some risks that could occur during the pre-contract, contract and post-contract phases of the outsourcing life cycle. It is anticipated that by understanding these risks, project managers could better manage them and subsequently increase the possibility of the success of outsourcing project. A systematic literature review of studies on software development outsourcing published in year 2005 to year 2015 was conducted. Of 41 studies consulted, 18 were concerned with outsourcing software development risk factors. The top three risk factors identified are lack of required technical skills and competencies (61%), lack of communication (44%) and poorly articulated requirements (44%). Â Â